Plant Extracts and Phytochemicals from the Asteraceae Family with Antiviral Properties - Borgo, Jimena; Wagner, Mariel S.; Laurella, Laura C.; Elso, Orlando G.; Selener, Mariana G.; Clavin, María; Bach, Hernán Gerónimo; Catalan, César A.N.; Bivona, Augusto E.; Sepúlveda, Claudia S.; Sülsen, Valeria P. (MDPI, 2024)
Asteraceae (Compositae), commonly known as the sunflower family, is one of the largest plant families in the world and includes several species with pharmacological properties. In the search for new antiviral candidates, an in vitro screening against dengue virus (DENV) was performed on a series of dichloromethane and methanolic extracts prepared from six Asteraceae species, including Acmella bellidioides, Campuloclinium macrocephalum, Grindelia pulchella, Grindelia chiloensis, Helenium radiatum, and Viguiera tuberosa, along with pure phytochemicals isolated from Asteraceae: mikanolide (1), eupatoriopicrin (2), eupahakonenin B (3), minimolide (4), estafietin (5), 2-oxo-8-deoxyligustrin (6), santhemoidin C (7), euparin (8), jaceidin (9), nepetin (10), jaceosidin (11), eryodictiol (12), eupatorin (13), and 5-demethylsinensetin (14). Results showed that the dichloromethane extracts of C. macrocephalum and H. radiatum and the methanolic extracts prepared from C. macrocephalum and G. pulchella were highly active and selective against DENV-2, affording EC50 values of 0.11, 0.15, 1.80, and 3.85 µg/mL, respectively, and SIs of 171.0, 18.8, >17.36, and 64.9, respectively. From the pool of phytochemicals tested, compounds 6, 7, and 8 stand out as the most active (EC50 = 3.7, 3.1, and 6.8 µM, respectively; SI = 5.9, 6.7, and >73.4, respectively). These results demonstrate that Asteraceae species and their chemical constituents represent valuable sources of new antiviral molecules.